2021
DOI: 10.1002/qua.26661
|View full text |Cite
|
Sign up to set email alerts
|

Arsenene, antimonene and bismuthene as anchoring materials for lithium‐sulfur batteries: A computational study

Abstract: Finding effective anchoring materials for the immobilization of soluble lithium polysulfides to suppress the shuttling effect has become the key to large-scale application of lithium-sulfur (Li-S) batteries. In this work, the potentials of group-VA twodimensional (2D) materials including arsenene, antimonene and bismuthene (As, Sb and Bi monolayers) as Li-S battery cathode anchoring materials were systematically investigated by density functional theory (DFT) calculations. The adsorption energies of sulfur (S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…4 monolayers are exothermic, implying the attractive interaction between them. We can see that the binding energies (E b ) of MSi 2 P 4 monolayers with the polysulfides are in the range of 0.81−3.55 eV, growing stronger with increasing lithiation, which is consistent with the evolution trend of E b in previous works 48,49. Considering the solubility of long-chain Li 2 S x in electrolytes, we examine the binding strengths between soluble LiPSs and typical electrolyte solvents (DOL, 1,3dioxolane; DME, 1,2-dimethoxyethane), and the corresponding data are plotted in Figure3a.…”
supporting
confidence: 90%
“…4 monolayers are exothermic, implying the attractive interaction between them. We can see that the binding energies (E b ) of MSi 2 P 4 monolayers with the polysulfides are in the range of 0.81−3.55 eV, growing stronger with increasing lithiation, which is consistent with the evolution trend of E b in previous works 48,49. Considering the solubility of long-chain Li 2 S x in electrolytes, we examine the binding strengths between soluble LiPSs and typical electrolyte solvents (DOL, 1,3dioxolane; DME, 1,2-dimethoxyethane), and the corresponding data are plotted in Figure3a.…”
supporting
confidence: 90%
“…[16] This offers a promising approach for controlling the surface structure of CoSe 2 and thereby the electrocatalytic activity. Besides, compared with the intensive theoretical works on the two-dimensional (2D) host materials, [17][18][19][20][21] heterojunctions, [22][23][24][25][26] single-atom catalytic effects, [27,28] surface modification, [20,29] and heteroatoms doping [30] for Li-S batteries, theoretical studies on the surface-dependent redox electrochemical performance for bulk materials for Li-S batteries are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…While pre-vious research has demonstrated its effectiveness as an electrode material for LIBs 53 and sodium-ion batteries, 54 recent studies have explored its potential for Li-S batteries. 44,49 However, pristine antimonene exhibits only weak to moderate adsorption capabilities of anchoring lithium pol-ysuldes in Li-S batteries. 44 To overcome this limitation, researchers have turned to doping strategies, with vanadium, tin, and selenium dopants showing promis-ing results through atom substitution.…”
Section: Introductionmentioning
confidence: 99%
“…SiC 2 , 39 V 2 CS 2 , 40 Ti 2 C 41 ) and monoelemental two-dimensional materials ( e.g. borophene, 42 phosphorene, 43 arsenene, 44 and bismuthene 44 ). Many of them exhibit weak interactions with lithium polysulfides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation